EFFORTS TO IMPROVE EMPLOYEES PERFORMANCE OF YOGYA STORE DEPARTMENT OF STORE YOGYA XXX BY INCREASING INFLUENCE BY LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE - Putri, Ratna Komala; Firdaus, Deri Rizki Maulana; Mulyani, Icha (CENTRAL ASIA AND THE CAUCASUS, 2022)
And one of the most important elements in an organization is human resources. Because human resources in a company are the key and the main factor that plays a very important role in moving a company in managing existing capital and available assets. But to achieve the goals of an organization, it takes a close relationship with the level of performance of its employees. Employee performance greatly affects the level of success in a company. Good employee performance will follow good results in the company's business development. Conversely, poor employee performance will also have a negative impact on the company's success. The results of this employee's performance can be assessed from the aspect of quality, quantity, working time and also cooperation in achieving the goals set by the company. It all depends on the quantity and also the time used by the employee in doing his job. Employee performance factors can also be seen from working time, delays, number of absences and length of service of employees. Employee performance is also built by Leadership style is one of the factors in order to improve employee performance, because basically the leader is the backbone of organizational development to encourage and influence good morale to employees. And employee performance is also influenced by a healthy organizational culture. This means that the better the organizational culture, the better the employee performance. On the other hand, if the organizational culture is not good, the employee's performance will decrease.